Middlemarch and “that Sort of Thing” - Farina, Jonathan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractMr. Brooke fails to become an elected political representative, but he nevertheless functions as a representative of Middlemarch society’s dominant mode of abstraction. Brooke’s comic idiom of “that sort of thing,” “that kind of thing,” and other variations of the word “thing” may be taken as a paradigm for George Eliot’s style throughout Middlemarch. Brooke parodies how characters and the narrator employ a grammar of things to articulate their relationships both to what they value in the material world and to their own interiority. I ascribe this grammar of things to what I call an “epistemology of character” because Eliot uses the same grammar of things to generate complex subjectivity within fully developed characters like Dorothea and Ladislaw as she does to describe scientific, conventional, religious, commercial, and physical realities.